Enhancing the Quality and Competitiveness of Indonesian Traditional Medicine Practitioners, Members of ASPETRI East Java, through Standardization - Wibowo, Teguh Setiawan; Larasaty, Hartaty; Lazuardi Ramadhan, Moh Risqy (Westscience Press, 2025)
Traditional medicine in Indonesia, particularly herbal concoctions known as jamu, holds significant potential in supporting public health. However, variations in quality and preparation methods can affect the efficacy and safety of the products. This community service activity aims to enhance the quality and competitiveness of traditional medicine practitioners who are members of ASPETRI East Java through standardization. The methods employed include delivering educational materials and hands-on practice in formulating jamu for various ailments, as well as introducing participants to simplisia and medicinal plants. The program is designed to improve participants' knowledge and skills in selecting high-quality raw materials, proper processing techniques, and standardized dosing. Evaluation is conducted through pre-tests and post-tests to assess knowledge improvement, along with participant satisfaction surveys regarding the content and training methods. It is anticipated that, through this initiative, traditional medicine practitioners will be able to produce jamu products that meet quality and safety standards, thereby increasing public trust and market competitiveness.